2002
DOI: 10.1038/sj.bjc.6600482
|View full text |Cite
|
Sign up to set email alerts
|

Weekly gemcitabine plus Epirubicin as effective chemotherapy for advanced pancreatic cancer: a multicenter phase II study

Abstract: The current role of chemotherapy in pancreatic carcinoma is limited, and progress in the treatment of this disease represents a significant challenge to medical oncology. The most promising drug under study is gemcitabine, a relatively new antimetabolite that represents an attractive candidate for combination chemotherapy because of its excellent side-effect profile and the absence of overlapping toxicities with other chemotherapeutic agents. Combined administration of gemcitabine and anthracyclines could resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Our experience with GEM and EPI clearly demonstrated that this combination is adequately tolerated with moderate toxicities that were qualitatively and quantitatively similar to those reported from other trials (Scheithauer et al, 1999;Neri et al, 2002;Reni et al, 2005).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our experience with GEM and EPI clearly demonstrated that this combination is adequately tolerated with moderate toxicities that were qualitatively and quantitatively similar to those reported from other trials (Scheithauer et al, 1999;Neri et al, 2002;Reni et al, 2005).…”
Section: Discussionsupporting
confidence: 85%
“…Neri et al (2002) reported an overall response rate of 25% and a SD in 41% of their patients. Most patients (77%) in that study were stage IV and two-thirds had a mean KPS between 70 and 80.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ross et al, 2002) or pancreatic cancer (e.g. Neri et al, 2002). They formed part of the FAM (5-FU, doxorubicin, MMC) and FAMtx (5-FU, doxorubicin, methotrexate) regimens, respectively.…”
Section: Discussionmentioning
confidence: 99%